Menjawab Tantangan Transformasi Digital: Implikasi Kepemimpinan Transformasional terhadap Adopsi Teknologi Digital - Octoyuda, Edgar; Siagian, Hendra Sakti Putra; Putri, Hidayatna (Ekonomi dan Bisnis, 2023)
Leadership is essential for corporate to strive the MSMEs to adopt the digital technology. However, the topic of how MSMEs managers may integrate the four dimensions of transformational leadership to increase adoption in the digital transformation era remains unanswered. This study investigates the role of transformative leadership in predicting MSMEs' adoption of digital technology. The research preposition was explored by a sample of 203 Indonesian MSMEs' employees. The fuzzy set qualitative comparative analysis (fsQCA) method was used to study the complex causality of transformational leadership in the adoption of digital technologies by MSMEs. The appropriate configurations connected to high agility were discovered by FsQCA, and this study concluded that idealized influence, inspirational motivation, and individual consideration will lead MSMEs to attain adoption of digital technology. This study provides theoretical and managerial guidance to scholars and managers interested in examining organizational adoption of digital technology in the MSME sector through the use of the four dimensions of transformational leadership. Following that, other theoretical contributions, practical implications, and future directions are considered.